Dynamic modulus by transversal vibrations of the wood of Abies sachalinensis (todomatsu) and Ostrya japonica (asada) - Sotomayor Castellanos, Javier Ramón (2025)
The modulus of elasticity of wood is an essential parameter in structural analysis, particularly in limit state methodologies and probabilistic methods. This study aimed to determine and contrast the densities and dynamic moduli of Abies sachalinensis and Ostrya japonica through non-destructive tests, to identify correlations between these properties. A total of 32 specimens of each species were prepared. The density and moisture content were determined according to ISO standards, and transverse vibration tests were conducted using an FFT analyzer. The results showed that O. japonica has a density 58% higher than that of A. sachalinensis, while the dynamic modulus of the latter is 39% higher. Statistical evaluations indicate significant differences between species in both density and dynamic modulus. Additionally, differentiated anatomical structures were identified that justify the variations in mechanical properties. The obtained values were positioned in relation to bibliographic data of woods from Mexico and India, highlighting O. japonica for its relatively high density and A. sachalinensis for its behavior similar to international trends. This study demonstrates the feasibility of using non-destructive dynamic methods to mechanically characterize little-studied woods, providing valuable information for their application in structural design, industrialization, and the development of value-added products.